Method for initiating macromolecular polymerization coating on explosive surface based on zwitter-ions
By using zwitterion-induced polymerization coating method on the surface of the explosive, the problems of low coating strength and harsh reaction conditions of explosive surface modification in the prior art are solved, and a simple and easy-to-operate coating process is achieved at room temperature, which significantly improves the interface effect between the explosive and the binder and the mechanical properties of the mixed explosive.
Patent Information
- Application Number
- CN202510561921.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-11
AI Technical Summary
In the prior art, explosive surface modification methods have low coating strength, easy shedding, harsh reaction conditions and safety challenges, making it difficult to effectively improve the mechanical properties of PBX.
Using a polymer polymerization coating method based on zwitterionic induced on the surface of the explosive, a dense and uniform coating layer is formed by spontaneous polymerization of 4-aminostyrene in an aqueous acid anion solution, thereby enhancing the interface interaction between the explosive and the binder.
A simple and easy-to-operate coating process at room temperature is achieved, the bonding strength between explosives and binders and the mechanical properties of mixed explosives are improved, and the interface effect is significantly enhanced.
Smart Images

Figure CN120289257A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for polymerizing and coating the surface of an explosive and its application, belonging to the technical field of energetic materials, and specifically relates to a method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation. Background Art
[0002] Polymer Bonded Explosive (PBX) is a highly filled energetic composite system composed of explosive crystals, a small amount of polymer binder, functional additives, etc., and is widely used in various weapons and equipment. During the use of PBX explosives, they will face complex environmental temperatures and stress states, requiring them to have good mechanical bearing capacity to resist the deformation, damage, and failure caused by complex stresses. However, as a typical polymer matrix composite with high particle filling, PBX exhibits a typical brittle and low-strength mechanical behavior. This is because small molecule explosive crystals in PBX generally have problems such as low surface energy and smooth surfaces, resulting in high inert characteristics on their surfaces, weak interactions with general binders, and easy debonding, thus affecting the mechanical behavior.
[0003] To improve the surface properties of explosives and enhance the interfacial interaction with binders, US Patent US4350542 and the literature (Energetic Materials, 2021, 11, 1076 - 1079) used coupling agents to coat and modify the surface of explosives to improve their interaction with binders. Patents CN106631639A and CN108658710A disclose a method for coating explosives with polyphenols to achieve the purpose of improving the surface wettability of explosives. On this basis, patents CN110078850A, CN109369315B, and CN109734547B all reported methods for grafting polymers on the surface of explosives through chemical reactions, further improving the explosive-binder interfacial interaction and mechanical properties.
[0004] However, in the above-disclosed technologies, there are still problems and challenges in the surface modification of explosives, and the expected performance has still not been achieved. For example, the coupling agent has the phenomena of low coating strength and easy shedding; the polyphenol-coated explosives are strongly dependent on the oxidation degree / time of catechol and the pH value of the medium; the synthesis route in the chemical grafting reaction on the surface of explosives is complex, the reaction conditions are relatively harsh, and it also involves a large amount of solvents, and the heating reaction conditions also pose challenges to the safety performance of explosives. Therefore, developing a new method for regulating the surface and interface of explosives is of great significance for improving the interface and enhancing the mechanical properties of PBX. Summary of the Invention
[0005] In order to overcome the defects existing in the surface modification and regulation of explosives in the prior art, the present invention provides a method for polymerizing and coating on the surface of explosives based on zwitterions, which has the advantages of mild reaction, simple process, strong universality, good coating effect, etc. It can form a dense, uniform and toughened coating layer structure on the surface of inert explosives. When applied to composite explosives, it can significantly improve the mechanical properties, which is of great significance.
[0006] The present invention solves the above problems through the following technical solutions:
[0007] A method for polymerizing and coating on the surface of explosives based on zwitterions, comprising the following steps: Step (1): Pre-modification of the explosive surface: First, the explosive surface is pre-modified with 4-aminostyrene monomer to make the reactive monomer 4-aminostyrene evenly distributed on the explosive surface, and a modified explosive with pre-modified 4-aminostyrene on the surface is obtained; Step (2): Preparation of an acidic polyanion aqueous solution: The water-soluble acidic anionic polymer is dissolved in water to prepare a polyanion aqueous solution, and the pH value of the polyanion aqueous solution is maintained at 2-4.5; Step (3): In-situ polymerization coating on the explosive surface: The pre-modified explosive in Step (1) is placed in the acidic polyanion aqueous solution in Step (2), stirred and dispersed at room temperature for 5 min to 30 min. Under the initiation of the acidic anionic polymer, 4-aminostyrene spontaneously polymerizes through the zwitterion mechanism to coat the explosive, and a polymer-coated explosive is obtained.
[0008] The method further includes: Based on the polymer-coated explosive obtained in Step (3), a composite explosive is prepared.
[0009] As a further improvement of the present invention, the explosive is water-insoluble and includes any one of 1,3,5-triamino-2,4,6-trinitrobenzene, cyclotrimethylenetrinitramine, octogen, hexanitrohexaazaisowurtzitane, 1,1-diamino-2,2-dinitroethylene.
[0010] As a further improvement of the present invention, before the 4-aminostyrene in Step (1) is used to pre-modify the explosive, it is also dissolved in ethanol for dilution, with a mass concentration of 2-6%, and then added to the explosive, and uniformly stirred and dispersed. After the ethanol volatilizes, a modified explosive with pre-modified 4-aminostyrene on the surface is obtained.
[0011] As a further improvement of the present invention, in Step (1), the total amount of 4-aminostyrene used is 1%-4% of the mass of the explosive.
[0012] As a further improvement of the present invention, in the step (1), it further includes: before using 4-aminostyrene to pre-modify the explosive, using a polyphenol compound to modify the surface of the explosive in a weakly alkaline aqueous solution to introduce multi-functional functional groups, so as to enhance the interaction between the explosive and the 4-aminostyrene modification layer.
[0013] As a further improvement of the present invention, in the step (1), the polyphenol compound is any one of dopamine hydrochloride, tannic acid or catechol, with a concentration of 1-3 g / L, a pH value of 8-9, and the time for surface modification of the explosive under stirring and dispersion conditions is 0.5-2 h.
[0014] As a further improvement of the present invention, in the step (2), the acidic anionic polymer is any one of polyacrylic acid, polyphosphoric acid, polystyrene sulfonic acid, polyitaconic acid, formulated into an anionic aqueous solution, and the molar ratio of the acidic anionic functional group to 4-aminostyrene is 2-1, and the pH value of the aqueous solution is maintained at 2-4.5, and the pH value is adjusted by dilute hydrochloric acid.
[0015] As a further improvement of the present invention, in the step (3), the 4-aminostyrene on the surface of the explosive rapidly and spontaneously polymerizes through the zwitterionic mechanism, the stirring time is 5 min to 30 min, the stirring speed is 200 r / min to 800 r / min, and then the dispersion is filtered and washed, washed 3-5 times with distilled water, and then the washed material is placed in an oven for drying, at a temperature of 50-70 °C and a time of 3 h to 12 h, and the polymer-coated explosive is obtained.
[0016] As a further improvement of the present invention, the preparation method of the composite explosive is any one of water suspension granulation, direct kneading granulation, and casting molding.
[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0018] (1) The preparation method and process of the coated explosive of the present invention are simple, only need to be stirred in an aqueous solution at room temperature to complete, are simple and easy to operate, have a short reaction time, can realize the polymer coating on the surfaces of different explosives, and have universality;
[0019] (2) The present invention can achieve all-round uniform and tight coating of the explosive, has a high bonding strength, and does not affect the original physical and chemical, safety, morphology and other properties of the explosive itself;
[0020] (3) When the present invention is applied to composite explosives, the prepared modified explosives can have multiple physical and chemical interactions with the binder, and can enhance the interfacial interaction strength between the explosive and the binder and the mechanical properties of the composite explosive. Description of the Drawings
[0021] Figure 1 Schematic diagram for the preparation of a novel tough interfacial coating layer on the surface of the explosive of the present invention;
[0022] Figure 2 SEM photograph of post-polymerization coating on the surface of the explosive of the present invention. Detailed implementation manners
[0023] To make the objectives, technical solutions and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be described in more detail below with reference to the drawings in the preferred embodiments of the present application. In the drawings, the same or similar reference numerals denote the same or similar components or components with the same or similar functions throughout. The described embodiments are some but not all of the embodiments of the present application. The embodiments described below with reference to the drawings are exemplary and are intended to explain the present application, and should not be construed as a limitation to the present application. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present application without creative efforts fall within the scope of protection of the present application.
[0024] In the description of the present application, it should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or display that includes a series of steps or units does not necessarily limit to the clearly listed steps or units, but may include other steps or units that are not clearly listed or are inherent to these processes, methods, products or displays.
[0025] The embodiments of the present application will be described in detail below with reference to the drawings. It should be noted that the following embodiments are only used to explain the present application and do not constitute a limitation to the present application.
[0026] It has been found that the polymerization of pure 4-aminostyrene (4-AS) is very difficult, and the charge density transfer from the amino group to the conjugated vinyl group inhibits the reaction of the latter with the initiator radical or the growing polymer chain. When 4-AS and 4-AS salt coexist, spontaneous polymerization can be initiated by the zwitterionic mechanism, which is generated by the nucleophilic attack of 4-AS at the β-position of the double bond activation on the 4-AS salt. In addition, the presence of acidic anionic polymers not only provides a salt-forming medium for the spontaneous polymerization of 4-AS, but also shortens the distance between monomers, thereby accelerating the self-polymerization of 4-AS. Therefore, a dense and tough coating layer can be formed on the surface of the explosive by using this simple self-polymerization reaction property, and the interfacial interaction can be significantly enhanced by the abundant functional groups on its surface, thereby improving the mechanical properties of PBX.
[0027] Example 1:
[0028] In this example, a method for polymer coating on the surface of an explosive based on zwitterionic initiation includes the following steps:
[0029] Step (1): Pre-modification of the explosive surface: Weigh 1.5 g of 4-AS and add it to 73.5 g of ethanol for dissolution, with a mass concentration of 2-6%; then weigh 50 g of TATB, and then add the ethanol solution containing 4-AS to the TATB explosive, and stir and disperse it evenly. After the ethanol volatilizes, a modified explosive with 4-AS pre-modified on the surface is obtained; that is, use 4-AS monomer to pre-modify the surface of TATB to make the reactive monomer 4-AS evenly distributed on the surface of TATB, laying a foundation for the subsequent in-situ spontaneous reaction.
[0030] In this example, the total amount of 4-AS used is 1%-4% of the mass of the explosive.
[0031] In step (1), an optional better scheme is included: Before using 4-AS to pre-modify the explosive, the surface of the explosive can be modified with polyphenolic compounds in a weakly alkaline aqueous solution to introduce multifunctional functional groups and further enhance the interaction between the explosive and the 4-AS modification layer.
[0032] Furthermore, the polyphenolic compound is any one of dopamine hydrochloride, tannic acid or catechol, with a concentration of 1-3 g / L, a pH value of 8-9, and the time for surface modification of the explosive under stirring and dispersion conditions is 0.5-2 h.
[0033] Step (2): Prepare an acidic polyanion aqueous solution: Weigh 3.03 g of an acidic anion polymer with a concentration of 30% such as polyacrylic acid PAA solution, add it to a certain amount of water, and prepare a polyanion aqueous solution with a certain concentration. Control the pH value of the polyanion aqueous solution to be maintained at 2-4.5 by adding water for dilution or dilute HCL. Preferably, in this example, the pH value of the polyanion aqueous solution is about 3.
[0034] Among them, the acidic anion polymer is any one of polyacrylic acid (PAA), polyphosphoric acid (PPA), polystyrene sulfonic acid (PSS), and polyitaconic acid (PIA). A polyanion aqueous solution with a certain concentration is prepared, and the molar ratio of the acidic anion functional group to 4-AS is 2-1. The pH value of the aqueous solution is maintained at 2-4.5, and the pH value can be adjusted with dilute hydrochloric acid.
[0035] Step (3): In-situ polymerization coating on the surface of explosives: Add the pre-modified TATB in step (1) to the polyanion aqueous solution in step (2), stir and disperse at room temperature. 4-AS on the surface of the explosives can rapidly and spontaneously polymerize through the zwitterionic mechanism without additional heating. The stirring time is 5 min to 30 min, and the stirring speed is 200 r / min to 800 r / min. Then, filter and wash the dispersion, wash it 3 - 5 times with distilled water, and then place the washed material in an oven for drying at a temperature of 50 - 70 °C for 3 h to 12 h to obtain the polymer-coated explosives. Under the initiation of acidic anionic polymers, 4-aminostyrene spontaneously polymerizes through the zwitterionic mechanism to coat the explosives.
[0036] In this example, preferably, the stirring speed is 400 r / min and the time is 20 min. Then, filter and wash the dispersion, wash it 3 times with distilled water, and then place the washed material in an oven for drying at a temperature of 60 °C for 8 h to obtain the polymer-coated TATB explosives.
[0037] Preferably, the polymer-coated TATB explosives obtained in Example 1 are prepared by any one of water suspension granulation, direct kneading granulation, and casting molding in a mass ratio of 95% modified explosive crystals to 5% fluorine-containing binder to obtain the mixed explosives with improved mechanical properties. In this example, water suspension granulation is used for preparation.
[0038] Of course, the explosives are water-insoluble explosives, including any one of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB), cyclotrimethylenetrinitramine (RDX), octogen (HMX), hexanitrohexaazaisowurtzitane (CL-20), and 1,1-diamino-2,2-dinitroethylene (FOX-7).
[0039] Example 2:
[0040] In this example, a method for polymer coating on the surface of explosives based on zwitterionic initiation includes the following steps:
[0041] Step (1): Pre-modification of the surface of explosives: Weigh 2 g of 4-AS, add it to 40 g of ethanol for dissolution, then weigh 50 g of TATB, and then add the ethanol solution containing 4-AS to the explosives and stir evenly to disperse. After the ethanol volatilizes, the modified explosives with 4-AS pre-modified on the surface can be obtained.
[0042] Step (2): Prepare an acidic polyanion aqueous solution: Weigh 4.5 g of a 30% polyacrylic acid PAA solution, add it to a certain amount of water, and prepare a polyanion aqueous solution with a certain concentration. Control the pH value of the solution to 2 by adding water for dilution or dilute HCl.
[0043] Step (3): In-situ polymerization coating on the surface of the explosive: Add the pre-modified TATB in step (1) to the aqueous PAA solution in step (2), stir and disperse at room temperature, with a stirring speed of 800 r / min for 10 min. Then, perform suction filtration and washing on the dispersion, wash 5 times with distilled water, and then place the washed material in an oven for drying at a temperature of 60 °C for 12 h to obtain the polymer-coated TATB explosive.
[0044] Prepare the polymer-coated TATB explosive obtained in Example 2 by direct kneading granulation at a mass ratio of 95% modified explosive crystals and 5% fluorine-containing binder to obtain the mixed explosive with improved mechanical properties.
[0045] Example 3:
[0046] In this example, a method for polymer coating on the surface of an explosive based on zwitterion-initiated polymerization includes the following steps:
[0047] Step (1): Pre-modification of the explosive surface: Weigh 50 g of TATB and add it to 800 mL of a weakly alkaline aqueous solution with a pH value of 8.5, stir and disperse. Then, dissolve dopamine hydrochloride with a concentration of 2 g / L, stir for 2 h, perform water washing and suction filtration for later use. Then, weigh 2 g of 4-AS, dissolve it in 50 g of ethanol, add the explosive to the ethanol solution containing 4-AS, stir and disperse evenly. After the ethanol evaporates, the modified explosive with 4-AS pre-modified on the surface can be obtained.
[0048] Step (2): Prepare an acidic polyanion aqueous solution: Weigh 6.0 g of a 30% polyacrylic acid (PAA) solution, add it to a certain amount of water, and prepare a polyanion aqueous solution with a certain concentration. Control the pH value of the solution to 2 by adding water for dilution or dilute HCl.
[0049] Step (3): In-situ polymerization coating on the surface of the explosive: Add the pre-modified TATB in step (1) to the aqueous PAA solution in step (2), stir and disperse at room temperature, with a stirring speed of 600 r / min for 20 min. Then, perform suction filtration and washing on the dispersion, wash 4 times with distilled water, and then place the washed material in an oven for drying at a temperature of 70 °C for 5 h to obtain the polymer-coated TATB explosive.
[0050] Prepare the polymer-coated TATB obtained in Example 3 by direct kneading granulation at a mass ratio of 95% modified explosive crystals and 5% fluorine-containing binder to obtain the mixed explosive with improved mechanical properties.
[0051] Example 4:
[0052] In this embodiment, a method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation includes the following steps:
[0053] Step (1): Pre-modification of the explosive surface: Weigh 0.5 g of 4-AS, dissolve it in 20 g of ethanol, then weigh 50 g of HMX. After that, add the ethanol solution containing 4-AS to the explosive and stir evenly to disperse. After the ethanol volatilizes, the modified explosive with 4-AS pre-modified on the surface can be obtained.
[0054] Step (2): Prepare an acidic polyanion aqueous solution: Weigh 2.7 g of a 30% polyitaconic acid (PIA) solution, add it to a certain amount of water to prepare a polyanion aqueous solution with a certain concentration, and control the pH value of the solution to 4.5 by diluting with water or dilute HCl.
[0055] Step (3): In-situ polymerization coating on the explosive surface: Add the pre-modified HMX in step (1) to the PIA aqueous solution in step (2), stir and disperse at room temperature, with a stirring speed of 500 r / min for 30 min. Then, filter and wash the dispersion, wash it 3 times with distilled water, and then place the washed material in an oven for drying at a temperature of 70 °C for 3 h to obtain the polymer-coated HMX explosive.
[0056] Disperse the polymer-coated HMX explosive obtained in Example 1 in a mixture of hydroxyl-terminated polybutadiene and TDI with a solid content of 85%. After curing, the mixed explosive with improved mechanical properties can be obtained.
[0057] Example 5:
[0058] In this embodiment, a method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation includes the following steps:
[0059] Step (1): Pre-modification of the explosive surface: Weigh 1.5 g of 4-AS, dissolve it in 23.5 g of ethanol, then weigh 50 g of FOX-7. After that, add the ethanol solution containing 4-AS to the explosive and stir evenly to disperse. After the ethanol volatilizes, the modified explosive with 4-AS pre-modified on the surface can be obtained.
[0060] Step (2): Prepare an acidic polyanion aqueous solution: Weigh 8.2 g of a 30% polyphosphoric acid (PPA) solution, add it to a certain amount of water to prepare a polyanion aqueous solution with a certain concentration, and control the pH value of the solution to 2 by diluting with water or dilute HCl.
[0061] Step (3): In-situ polymerization coating on the surface of the explosive: Add the pre-modified FOX-7 in step (1) to the PPA aqueous solution in step (2), stir and disperse at room temperature, with a stirring speed of 200 r / min for 5 min. Then, perform suction filtration and washing on the dispersion, wash 4 times with distilled water, and then place the washed material in an oven for drying at a temperature of 60 °C for 12 h to obtain the polymer-coated FOX-7 explosive.
[0062] Prepare the polymer-coated FOX-7 explosive obtained in Example 5 by water suspension granulation at a mass ratio of 95% modified explosive crystals to 5% fluorine-containing binder to obtain the mixed explosive with improved mechanical properties.
[0063] Example 6:
[0064] In this example, a method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation includes the following steps:
[0065] Step (1): Pre-modification of the explosive surface: Weigh 50 g of CL-20 and add it to 800 mL of a weakly alkaline aqueous solution with a pH value of 9.0, stir and disperse. Then dissolve tannic acid with a concentration of 1.5 g / L and FeCl3 with a concentration of 0.12 g / L, stir for 2 h, then perform water washing and suction filtration for later use. Then weigh 1.5 g of 4-AS, dissolve it in 50 g of ethanol, add the explosive to the ethanol solution containing 4-AS, stir and disperse evenly. After the ethanol volatilizes, the modified explosive with 4-AS pre-modified on the surface can be obtained.
[0066] Step (2): Prepare an acidic polyanion aqueous solution: Weigh 7.7 g of polystyrene sulfonic acid PSS with a concentration of 30%, add it to a certain amount of water, prepare a polyanion aqueous solution with a certain concentration, and control the pH value of the solution to 3.0 by adding water for dilution or dilute HCl.
[0067] Step (3): In-situ polymerization coating on the surface of the explosive: Add the pre-modified TATB in step (1) to the PAA aqueous solution in step (2), stir and disperse at room temperature, with a stirring speed of 600 r / min for 20 min. Then, perform suction filtration and washing on the dispersion, wash 4 times with distilled water, and then place the washed material in an oven for drying at a temperature of 60 °C for 10 h to obtain the polymer-coated CL-20 explosive.
[0068] Prepare the polymer-coated CL-20 explosive obtained in Example 6 by water suspension granulation at a mass ratio of 95% modified explosive crystals to 5% polyurethane binder to obtain the mixed explosive with improved mechanical properties.
[0069] Control appendix Figure 1-2The modified explosive prepared in the embodiment of the present invention was analyzed. As can be seen from the appended Figure 2 It can be seen that the surface of the modified explosive is evenly and densely coated with a layer of polymer. There is an obvious polymer covering on the originally smooth surface of the explosive, and there are also some small protrusions, which increase the coupling effect between the explosive and the binder.
[0070] Table 1 shows the comparison of the mechanical properties between the modified TATB-based mixed explosives obtained in Specific Embodiment 2 and Specific Embodiment 3 of the present invention and the original unmodified mixed explosives.
[0071] Table 1 Comparison of the Mechanical Properties between the Original Unmodified TATB-Based and Polymer-Coated Mixed Explosives
[0072]
[0073]
[0074] As can be seen from Table 1, after the surface of the explosive is coated with a polymer by zwitterionic-initiated polymerization to prepare a mixed explosive, the mechanical properties are significantly improved. Compared with the original unmodified sample, in Example 3, the Brazilian tensile fracture strength and compressive strength reached 9.65 MPa and 45.07 MPa respectively, with increases of 55.39% and 66.74% respectively, showing a remarkable improvement effect.
[0075] Although the present invention has been described herein with reference to its illustrative embodiments, the above embodiments are only the preferred embodiments of the present invention. The embodiments of the present invention are not limited by the above embodiments. It should be understood that those skilled in the art can design many other modifications and embodiments, which will fall within the scope and spirit of the principles disclosed in this application.
Claims
1. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation, characterized in that, It includes the following steps: Step (1): Surface pre-modification of explosives: First, use 4-aminostyrene monomer to pre-modify the surface of explosives, so that the reactive monomer 4-aminostyrene is evenly distributed on the surface of explosives, and the modified explosives with surface 4-aminostyrene pre-modification are obtained; Step (2): Prepare an acidic polyanion aqueous solution: Dissolve the water-soluble acidic anionic polymer in water to prepare a polyanion aqueous solution, and keep the pH value of the polyanion aqueous solution at 2-4.5; Step (3): In-situ polymerization coating on the surface of explosives: Place the pre-modified explosives in step (1) into the acidic polyanion aqueous solution in step (2), stir and disperse at room temperature for 5 min to 30 min. Under the initiation of the acidic anionic polymer, 4-aminostyrene spontaneously polymerizes through the zwitterionic mechanism to coat the explosives, and the polymer-coated explosives are obtained.
2. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation, as claimed in claim 1, wherein: It also includes: Based on the polymer-coated explosives obtained in step (3), prepare a mixed explosive.
3. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation according to claim 1, characterized in that, The explosive is water-insoluble and includes any one of 1,3,5-triamino-2,4,6-trinitrobenzene, cyclotrimethylenetrinitramine, octogen, hexanitrohexaazaisowurtzitane, 1,1-diamino-2,2-dinitroethylene.
4. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation, according to claim 1, characterized in that, Before pre-modifying the explosives with 4-aminostyrene in step (1), 4-aminostyrene is also dissolved in ethanol for dilution, with a mass concentration of 2-6%, and then added to the explosives, stirred and dispersed evenly. After the ethanol volatilizes, the modified explosives with surface 4-aminostyrene pre-modification are obtained.
5. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation, as claimed in claim 1, wherein In step (1), the total amount of 4-aminostyrene used is 1%-4% of the mass of the explosives.
6. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation according to claim 1, characterized in that, In step (1), it also includes: Before using 4-aminostyrene to pre-modify the explosives, use polyphenolic compounds to modify the surface of the explosives in a weakly alkaline aqueous solution to introduce multifunctional functional groups to enhance the interaction between the explosives and the 4-aminostyrene modification layer.
7. A method for polymer encapsulation initiation based on zwitterions on the surface of explosives according to claim 6, characterized in that, In step (1), the polyphenolic compound is any one of dopamine hydrochloride, tannic acid or catechol, with a concentration of 1-3 g / L, a pH value of 8-9, and the time for surface modification of the explosives under stirring and dispersion conditions is 0.5-2 h.
8. A method for polymerizing and coating on the surface of an explosive based on zwitterion initiation, according to claim 1, characterized in that In step (2), the acidic anionic polymer is any one of polyacrylic acid, polyphosphoric acid, polystyrene sulfonic acid, polyitaconic acid. Prepare a polyanion aqueous solution, and the molar ratio of the acidic anionic functional group to 4-aminostyrene is 2-1. The pH value of the aqueous solution is kept at 2-4.5, and the pH value is adjusted with dilute hydrochloric acid.
9. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation, according to claim 1, characterized in that In step (3), 4-aminostyrene on the surface of the explosives rapidly polymerizes spontaneously through the zwitterionic mechanism. The stirring time is 5 min to 30 min, and the stirring speed is 200 r / min to 800 r / min. Then, the dispersion liquid is filtered and washed, washed 3-5 times with distilled water, and then the washed material is placed in an oven for drying, with a temperature of 50-70 °C and a time of 3 h to 12 h, and the polymer-coated explosives are obtained.
10. A method for polymerizing and coating on the surface of an explosive based on zwitterionic initiation according to claim 2, characterized in that, The preparation method of the mixed explosive is any one of water suspension granulation, direct kneading granulation, and casting molding.
Citation Information
Patent Citations
Method for improving the surface wettability of energetic material and the mechanical property of explosive
CN106631639A
Method for improving mechanical properties of melt-cast explosive
CN108658710A
A hyperbranched high-strength energetic composite
CN109369315B
An in-situ hyperbranched polyester grafted modified explosive, its preparation method and application
CN109734547B
Method for atomically transferring radical polymerization grafting polymer on surface of explosive
CN110078850A